Strong seasonality in diets and alarming levels of food insecurity and child malnutrition in south-eastern Madagascar - Rousseau, Samuel; Steinke, Jonathan; Vincent, Méloé; Andriatseheno, Hanitriniavo; Pontarollo, Julie (Frontiers in Sustainable Food Systems, 2023)
Rural areas of Madagascar face a tense food and nutrition security situation. The country reports some of the highest rates of undernourishment and malnutrition worldwide. Evidence is scant, however, about how the rural people’s diets vary over the course of the agricultural year, and how different household types deal with fluctuating food availability. This lack of detailed understanding of the food and nutrition security situation across time and social strata currently limits development stakeholders’ ability to tailor interventions to local needs. Using randomly sampled survey data from Farafangana District in south-eastern Madagascar, this study analyzes rural households’ diets across three time points within one year (minor lean period, major lean period, main post-harvest period). In addition, anthropometric data on children aged 6–59 months were collected during the major lean period to determine levels of chronic and acute child malnutrition. Overall, food insecurity stood at high levels at all times, but with substantial variation across the year. Shortly before the main rice harvest, the prevalence of moderate and severe food insecurity was 78%, twice as high as shortly after harvest. With 57% of children stunted and a 17% prevalence of wasting, the observed levels of chronic and acute child malnutrition exceed levels reported previously. By studying what households eat and how they source it (own production vs. purchases), we found distinct patterns of food acquisition between the three periods. Diminishing food security is reflected by substituting rice by cassava, unripe jackfruit (minor lean period), and local tuber tavolo (major lean period), as well as by lower diversity of side dishes. Our results underline the need for long-term agricultural development strategies that contribute to greater household food self-sufficiency especially during the lean periods. But the alarming level of acute child malnutrition also calls for more immediate humanitarian aid and public health interventions.